1974
DOI: 10.1182/blood.v43.3.389.389
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoid Nodules of Bone Marrow: Normal and Abnormal

Abstract: A study of consecutive bone marrow aspirates from 365 patients without lymphoproliferative disorder, ten patients with chronic lymphocytic leukemia (CLL), and 25 patients with malignant lymphoma disclosed a clear separation of normal from abnormal lymphoid nodules (LN). Normal LN were found in 47% of patients and were classified into lymphoid follicles and lymphoid infiltrates. A new entity, nodular lymphoid hyperplasia (NLH), was diagnosed on ten bone marrows which contained a low-power field displaying four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

1977
1977
1996
1996

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(12 citation statements)
references
References 8 publications
0
11
0
1
Order By: Relevance
“…The clinical features of WM are due to the presence of monoclonal IgM and the accumulation of lymphoid cells causing bone marrow failure and enlargement of the spleen, liver and lymph nodes. Nevertheless, as pointed out (19), the differential diagnosis of macroglobulinaemia may be very difficult, and in some cases is quantitative rather than qualitative (20). However, as previously shown (21) careful follow-up investigations and sequential biopsies will clarify the picture.…”
Section: Differential Diagnosis Of Wmmentioning
confidence: 89%
“…The clinical features of WM are due to the presence of monoclonal IgM and the accumulation of lymphoid cells causing bone marrow failure and enlargement of the spleen, liver and lymph nodes. Nevertheless, as pointed out (19), the differential diagnosis of macroglobulinaemia may be very difficult, and in some cases is quantitative rather than qualitative (20). However, as previously shown (21) careful follow-up investigations and sequential biopsies will clarify the picture.…”
Section: Differential Diagnosis Of Wmmentioning
confidence: 89%
“…When there is no lymph node or extranodal site with an independent tissue diagnosis, the diagnosis of malignant lymphoma should be made with great caution, since occasionally even extensive lymphoid aggregates may be found confined to the bone marrow of patients who do not have generalized lymphoma by clinical or pathological criteria. Rywlin et al [20] reported ten such patients with nodular lymphoid hyperplasia of the bone marrow and noted no progression of the disorder in all five of their patients available for study over a 2-2.S.year follow-up period. More recently Mennemeyer and Kjeldsberg [22] reported florid lymphoid replacement of the bone marrow in an 80-year-old man who had no autopsy evidence of ex tramedullary lymphoma nine months after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In general, both quantitative and qualitative factors help in this decision. In a recent review Rywlin et al [20] noted that the published frequency of benign lymph nodules in random bone marrow examinations ranged from 1-9% in aspirated or biopsy material and 21-62% in autopsy material. In their own series, however, the frequency was 47%, which they attributed to the higher age of their patients (71.9 years) and their marrow concen· tration technique.…”
Section: Discussionmentioning
confidence: 99%
“…Of the bone marrow biopsies with non-malignant infiltrates only those that contained well-defined lymphoid aggregates were considered in our study, excluding the purely interstitial lymphoid reactions. Their benign nature was based upon the classical criteria of number, size, localization, and cellular components 7,8 , associated with the immunohistochemical data 9,10 .…”
Section: Methodsmentioning
confidence: 99%